Practice and Research on Applying Business Simulation Software in Business Management Teaching - Li, Yaxing (Journal of Theory and Practice of Contemporary Education, 2023)
The training of Business Management in the past focused on theories teaching, accompanied by limited experimental training, is not conductive to the development of students' professional skills and innovative entrepreneurial abilities. In past, the practical training of Business Management revolved around classroom teaching,which was difficult to arouse students' interests nor contribute their knowledge of real businesses. The modern information technology provides the possibility for Business Management teaching to carry out more realistic practical training projects. Based on the model of students' self-regulated learning, Business Simulation Software is used in Business Management teaching in a lot of British universities. The software can help students understand how real businesses work in a fast-moving market by simulating business operations. It can help students practice management knowledge and theories and practice their professional skills.